Design of experiments for chemical, pharmaceutical, food, and industrial applications / Eugenia Gabriela Carrillo-Cedillo ...[et al] - Arredondo-Soto, Karina Cecilia editor
""This book seeks to increase the use of design of experiments to optimize and improve analytical methods and productive processes in order to use less resources and time"